2020
DOI: 10.1111/ctr.14088
|View full text |Cite
|
Sign up to set email alerts
|

Plasma mycophenolic acid concentration and the clinical outcome after lung transplantation

Abstract: The long-term survival rate of lung transplant recipients is still low compared with those of other solid organ transplant recipients, despite improvements in survival during the early phase after transplantation. The main cause of death after the first post-transplant year is chronic lung allograft dysfunction (CLAD), a clinical form of chronic lung allograft rejection developing in 50% of recipients at 5 years and in 76% at 10 years after lung transplantation. 1 Additionally, infectious complications are lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Better results can be obtained with an additional measurement after 4 h (C 4 ) and utilization of the following formula: AUC 0–12 = 8.217 + 3.163 × C 0 + 0.994 × C 1 + 1.334 × C 2 + 4.183 × C 4 . According to Yakubi et al, the preferred AUC 0–12 range lies between 22.8 and 40.5 μg × h/ml.” 57 – 59 TDM of mycophenolate mofetil represents a clinical-pharmacological challenge to physicians and is considerably more complex than conventional TDM. Several measurements of mycophenolate plasma levels after drug intake as well as the application of a multivariate linear regression equation are required.…”
Section: Resultsmentioning
confidence: 99%
“…Better results can be obtained with an additional measurement after 4 h (C 4 ) and utilization of the following formula: AUC 0–12 = 8.217 + 3.163 × C 0 + 0.994 × C 1 + 1.334 × C 2 + 4.183 × C 4 . According to Yakubi et al, the preferred AUC 0–12 range lies between 22.8 and 40.5 μg × h/ml.” 57 – 59 TDM of mycophenolate mofetil represents a clinical-pharmacological challenge to physicians and is considerably more complex than conventional TDM. Several measurements of mycophenolate plasma levels after drug intake as well as the application of a multivariate linear regression equation are required.…”
Section: Resultsmentioning
confidence: 99%
“…AUC analysis is not performed for mycophenolic acid, for which reason we cannot relate our results to the mycophenolic acid AUC. Yabuki et al found large variations in patients after solid organ transplantation [25]. In addition, they reported that the mycophenolic acid AUC showed only a weak correlation with MPA 0 or mycophenolate mofetil dosage [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Yabuki et al found large variations in patients after solid organ transplantation [25]. In addition, they reported that the mycophenolic acid AUC showed only a weak correlation with MPA 0 or mycophenolate mofetil dosage [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Due to fluctuating plasma concentrations of MMF, area under the curve (AUC) was established as a relevant parameter for bioavailability and therapeutic drug monitoring. The ideal AUC has been reported to be 40-60 µg × h/mL (Ferreira et al, 2020) after renal transplantation and about 30-40 µg × h/mL after lung transplantation (Yabuki et al, 2020). However, it should be noted that the bioavailability in these studies was chosen to establish sufficient immunosuppression with few side effects.…”
Section: The Brain Cytoprotective Effect Of Mycophenolate Mofetil Dep...mentioning
confidence: 99%